The Impact of Health Education through Animated Videos on Mothers' Attitudes in Providing Complementary Foods to Breast Milk - Nguyễn, Mạnh Cường; Le, Thanh Nguyen (Journal of Health Innovation and Environmental Education, 2025)
Purpose of the study: To determine the effect of health education through animated video toward mother’s behavior with infant aged 6-12 months to prevent stunting through the provision of complementary feeding.Methodology: This study employed pre experimental design with the one group pretest post test design. There were 20 respondents involved in this study which were selected by using probability sampling with simple random sampling. The data were collected by using questionnaire and analyzed by using parametric test praid T-Test.Main Findings: The finding showed that there was an effect of health education through animated video and mother behavior. Good Mother behavior in providing complementary feeding in infants aged 6 months could decrease the risk of stunting.Novelty/Originality of this study: This study offers novelty by integrating animated health education videos to strengthen mothers’ attitudes toward appropriate complementary feeding practices. Unlike previous studies that rely on conventional counseling, this research demonstrates how visual–digital media can enhance maternal understanding and behavioral readiness. The findings advance knowledge by highlighting animation-based education as an effective, scalable intervention for improving infant nutrition practices.